An Analysis of Students’ Linguistic and Performance Challenges in Performing Under the Gaslight by Augustine Daly - Eripuddin; Pipit Rahayu; Azi Nurazima Juhastri; Debora Martini Jai (English Lecturers and Teachers Association (ELTA), 2026)
This study investigate the Drama is as an effective pedagogical approach in English Language Teaching (ELT) due to its potential to promote communicative competence, learner engagement, and expressive skills. However, the use of classical English drama, particularly nineteenth-century texts, may pose significant challenges for EFL learners. This study aims to analyze the linguistic and performance-related difficulties experienced by 23 fifth-semester students of the English Education Study Program at Universitas Pasir Pengaraian in performing Under the Gaslight by Augustine Daly. Employing a descriptive qualitative research design, data were collected through classroom observations, semi-structured interviews, and documentation during rehearsal and performance sessions. The findings reveal that students encountered major difficulties involving both language and performance demands, including archaic vocabulary, complex sentence structures, pronunciation problems, stage fright, limited voice projection, inadequate body movement, and weak emotional delivery. These challenges were closely interconnected, with language barriers contributing to psychological anxiety and subsequently affecting overall performance quality. The study concludes that while drama remains a valuable instructional tool in ELT, the use of classical drama requires careful pedagogical mediation, including linguistic scaffolding, cultural contextualization, and systematic performance training. The findings are expected to contribute to the improvement of drama instruction, text selection, and teaching strategies in English teacher education programs, particularly in equipping prospective English teachers with the competence to implement drama-based learning effectively in future classrooms Keywords: Students’ Difficulties, Drama, Performance